PENGARUH KOMUNIKASI PEMASARAN, KEPERCAYAAN MEREK DAN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Produk Bubur Bayi Promina di Carrefour Wilayah Jakarta Selatan ) - Bintoro, Bintoro; Yuniawan, Ahyar; Sukresna, I Made (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2016)
Promina is a product food baby produced by PT Indofood CBP Sukses Makmur Tbk. under the auspices of Indofood Nutrition (for baby food division formerly known as PT Gizindo Prima Nusantara until the merger in 2010). Division of Nutrition & Special Foods was formed to help meet the nutritional needs of children Indonesia, through the provision of nutritious food products for infants and toddlers, as well as nutritious milk drink for pregnant women and nursing mothers.This research was conducted by analyzing the factors that influence purchasing decisions pap Promina with variable influence of marketing communications, brand trust and brand equity. This research by developing a theoretical model by proposing sauatu five hypotheses to be tested usingStructural Equation Model (SEM) as an analytical tool. Respondents of this research is all consumer buyers pap Careffour Promina in South Jakarta which amounted to 150 people.The results of data processing by using SEM to have met the theoretical model Godnessof Fit as follows: Value Chi Square = 255.588; df = 129; p = 5%; Probability = 0,000; GFI = 0.846; AGFI = 0,795; TLI = 0,959; CFI = 0.965; RMSEA = 0.081. The processing results can be stated that the model is feasible to use. The results of this study indicate that purchasing decisions can ditinggkatkan with marketing communications, brand trust and brand equity. Marketing communications and brand equity as well as trust high brand will influence purchasing decisions pap Promina in the Carrefour area of South Jakarta.